2016
DOI: 10.1007/s11307-016-1007-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of [18F]FSPG PET to Image Hepatocellular Carcinoma: First Clinical Evaluation in a US Population

Abstract: Purpose Non-invasive imaging is central to hepatocellular carcinoma (HCC) diagnosis; however, conventional modalities are limited by smaller tumors and other chronic diseases that are often present in patients with HCC, such as cirrhosis. This pilot study evaluated the feasibility of (4S)-4-(3-[18F]fluoropropyl)-L-glutamic acid ([18F]FSPG) positron emission tomography (PET)/X-ray computed tomography (CT) to image HCC. [18F]FSPG PET/CT was compared to standard-of-care (SOC) magnetic resonance imaging (MRI) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…[ 18 F]FSPG did not accumulate in the inflammatory model tested in animals [16], although subsequent clinical studies reported uptake in sarcoidosis [19]. Pilot clinical studies examining dosimetry and biodistribution in healthy volunteers [20,21] and tumor detection in patients with non-small cell lung cancer, hepatocellular carcinoma, and brain tumors showed promising results and confirmed preclinical data [22][23][24][25]. In particular, low background uptake in the brain, lung, and bowel was observed.…”
Section: Introductionmentioning
confidence: 75%
“…[ 18 F]FSPG did not accumulate in the inflammatory model tested in animals [16], although subsequent clinical studies reported uptake in sarcoidosis [19]. Pilot clinical studies examining dosimetry and biodistribution in healthy volunteers [20,21] and tumor detection in patients with non-small cell lung cancer, hepatocellular carcinoma, and brain tumors showed promising results and confirmed preclinical data [22][23][24][25]. In particular, low background uptake in the brain, lung, and bowel was observed.…”
Section: Introductionmentioning
confidence: 75%
“…We have recently developed monoclonal antibody agents against both CA9 and CA12 [ 25 ], there are numerous reports of CA9 targeted imaging agents [ 35 58 ], and there is a commercially available near-infrared (NIR) fluorescent carbonic anhydrase inhibitor-based agent (Hypoxisense, PerkinElmer). Two 18 F-glutamate derivative PET agents and an 18 F-aminosuberic acid derivative PET agent have also been developed that target the x C - transporter (SLC7A11) [ 62 69 ]. Recently, a fluorescent cystine derivative has also been developed for imaging the x C - transporter (SLC7A11) [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…is an L-glutamate derivative that is specifically taken up by system Xc in tumor models and cancer patients (27)(28)(29). A similar tracer targeting the Xc transporter system, 5-18 F-fluoro-aminosuberic acid, also demonstrated potential usefulness as a tracer for monitoring of upregulation of system Xc transporter and oxidative stress (30).…”
Section: Other Amino Acid Derivatives For Tumor Imagingmentioning
confidence: 99%